Scheduling and drop policies for traffic differentiation on vehicular delay-tolerant networks - Soares, V.N.G.J. (2009)
Vehicular Delay-Tolerant Networks (VDTNs) are a promising technology for vehicular communications, creating application scenarios that enable non-real time services with diverse performance requirements. Because of scarce network resources (e.g. bandwidth and storage capacity) and node’s short contact durations, the underlying VDTN network infrastructure must be capable of prioritizing traffic. This paper investigates several scheduling and drop policies, which can be used to implement traffic differentiation. Priority Greedy, Round Robin, and Time Threshold scheduling polices are proposed. In terms of drop policy, the message with the lowest priority and the lowest remaining time-to-live is discarded first. We evaluate their efficiency and tradeoffs, through simulation. The results presented in this paper can be used as a starting point for further studies in this research field, and give helpful guidelines for future VDTN protocol design.